Green card [videorecording (DVD)] - Depardieu, Gérard, 1948-; MacDowell, Andie; Neuwirth, Bebe (Kino Lorber, 2019)
Two strangers agree to a marriage of convenience, thinking it's going to be hassle-free. She'll get to live in the apartment of her dreams; he'll get to live in the U.S. But before they know it, the two opposites encounter far more difficulties than most married couples could ever imagine, and worse yet, this mismatched twosome just might be falling in love.